Earlier surgical intervention in congenital heart disease results in better outcome and resource utilization - Panni Roheena Z; Ashfaq Awais; Amanullah Muhammad M (BMC, 2011)
Abstract Background Congenital heart disease (CHD) accounts for a major proportion of disease in the pediatric age group. The objective of the study was to estimate the cost of illness associated with CHD pre, intra and postoperatively; among patients referred to a tertiary care hospital in Karachi, Pakistan. This is the first study conducted to estimate the cost of managing CHD in Pakistan. Methods A prevalence based cost of illness study design was used to estimate the cost of cardiac surgery (corrective & palliative) for congenital heart defects in children ≤ 5 years of age from June 2006 to June 2009. A total of 120 patients were enrolled after obtaining an informed consent and the data was collected using a pre-tested questionnaire. Results The mean age at the time of surgery in group A (1-12 mo age) was 6.08 ± 2.80 months and in group B (1-5 yrs) was 37.10 ± 19.94 months. The cost of surgical admission was found to be significantly higher in the older group, p = 0.001. The total number and cost of post-operative outpatient visits was also higher in group B, p = 0.003. Pre and post operative hospital admissions were not found to be significantly different among the two groups, p = 0.166 and 0.627, respectively. The number of complications were found to be different between the two groups (p = 0.019). Majority of these were contributed by hemorrhage and post-operative seizures. Conclusion This study concluded that significant expenditure is incurred by people with CHD; with the implication that resources could be saved by earlier detection and awareness campaigns.